PENGARUH ALKALISASI HYBRID COMPOSITE BULU ITIK ALABIO DAN SERAT PURUN TIKUS TRHADAP KEAUSAN DAN KEKERASAN - Akhmad Syarief; Dadang Aling Setiawan; Fadliyanur Fadliyanur (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2024)
South Kalimantan Province is the habitat for a type of plant known as Purun Tikus. This plant is traditionally used for handicrafts and serves as a habitat for Alabio ducks. Sodium hydroxide (NaOH) is an alkaline chemical compound that effectively removes and cleans residues in fibers. Therefore, this study investigates the composite materials reinforced with duck hair and Purun Tikus using an immersion alkalization method with NaOH. The objective of this research is to determine the effects of alkalization on a hybrid mixture of duck hair and Purun Tikus with a polyester matrix on wear and hardness properties, and to examine the influence of voids on perforated pores. The wear test was performed according to ASTM G99-04, and the hardness test followed the ASTM D-785 standard. Samples were prepared using the hand lay-up method with a composition of 78% polyester, 2% catalyst, and 20% reinforcement with a volume ratio of (10%:90%). The alkalization treatment times were set at 10, 20, 30, 40, 50, and 60 minutes using a 5% NaOH solution. The results indicated that the highest wear value was observed at the 10-minute alkalization time, while the lowest wear value was noted at the 60-minute alkalization time. Conversely, the highest hardness value was obtained at the 60-minute alkalization time, and the lowest at the 10-minute alkalization time. Therefore, alkalization time significantly affects the wear, hardness, and void properties of the composite materials.